A study on quilombola school education in the state of Alagoas / Um estudo sobre a educação escolar quilombola no estado de Alagoas - José Bezerra da Silva; Max Silva da Rocha (Universidade Estadual de Alagoas, 2016)
The Brazilian government committed to neoliberal capital provisions have set national education to those provisions. In the context of this project, there is the quilombola education system, which prioritizes the territory, ancestry, orality and the African worldview. State actions aimed at fulfilling the agendas of global conferences Education for All, held in 1990 and the Third Battle Conference against racism, discrimination and Related Intolerance, held in 2001. Despite the importance of this type of education and state responsibility with the population African descent, the State of Alagoas is not meeting those requirements, given the lack of commitment to the quilombo education of 64 existing communities in the state. With this article we want to explain the formation of the Quilombola School Education, highlighting its immense importance to the Maroons, their ties to neo-liberalism and the disinterest of the State of Alagoas with its implementation.